2015
DOI: 10.1186/s13098-015-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

High-risk alcohol use and anxiety and depression symptoms in adolescents and adults with type 1 diabetes mellitus: a cross-sectional study

Abstract: BackgroundThe medical literature shows that alcohol consumption is common among diabetic individuals and is associated with poor adherence to treatment, resulting in increased morbidity and mortality. However, no study has assessed the association between high-risk alcohol consumption and the presence of anxiety and depression in individuals with type 1 diabetes mellitus (1DM).MethodsThe present cross-sectional study was conducted in Uberlândia, Brazil, and it assessed 209 outpatients in relation to alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Various studies have documented that factors associated with depression among diabetes patients using the classical logistic regression. Risk factors were age [ 10 , 15 , 34 ], gender [ 14 , 15 , 35 38 ], marital status [ 15 , 35 , 37 , 39 ], educational status [ 34 , 37 , 40 ], hazardous drinking [ 38 , 39 ], medication adherence [ 13 , 39 ], duration lived with DM [ 9 , 14 , 35 ], fasting blood sugar [ 41 ], DM complication [ 10 , 12 , 14 , 36 , 37 ], chronic illness other than DM [ 14 , 34 ], and types of medication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have documented that factors associated with depression among diabetes patients using the classical logistic regression. Risk factors were age [ 10 , 15 , 34 ], gender [ 14 , 15 , 35 38 ], marital status [ 15 , 35 , 37 , 39 ], educational status [ 34 , 37 , 40 ], hazardous drinking [ 38 , 39 ], medication adherence [ 13 , 39 ], duration lived with DM [ 9 , 14 , 35 ], fasting blood sugar [ 41 ], DM complication [ 10 , 12 , 14 , 36 , 37 ], chronic illness other than DM [ 14 , 34 ], and types of medication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lloyd et al [ 44 ], using the same cut-off, found that 8% of the patients with diabetes scored above the cut-off for depression, thus in line with our study. Knychala et al [ 46 ] used the cut-off score of 8, and reported prevalence rates of 4.7% among males and 17.6% of females with diabetes. Given the lower cut-off, the higher prevalence rates compared to the previous two studies, can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk alcohol use was found in 12.9% of 14-19-year old subjects with T1DM in Brazil. There was no significant gender difference among this age group, while higher rates of high-risk alcohol use were seen in older age groups with males having greater high-risk use than females (29). Emerging adults with T1DM should be counseled of effects of alcohol on glucose and risk for hypoglycemia unawareness and delayed hypoglycemia (30,31).…”
Section: Substance Usementioning
confidence: 90%